Paint blistering affects quality of finished products. (October 2018) - Solomon, Nicolae; Solomon, Iulia
Abstract: Automotive painted components confront an almost limitless variety of environments and environmental assaults. The appearance (color, gloss, and texture) of the surface significantly affects a customer's perception of product quality. During the paint application process however, and later during car operation, numerous kinds of failures and/or paint damages can occur. A defective part from a car in warranty period with paint blisters was brought for investigations. Samples from defective part were taken, and then they were examined using optical microscopy and Fourier transform infrared spectroscopy (FTIR). A section of the part away from the blisters was excised and used as a reference. The black coating was analyzed in the reference area, on the rim of the part away from the blisters and on top of the coating covering the blisters. The result of the spectral subtraction revealed that benzyl benzoate was used inside of the car. Benzyl benzoate is used in topical medications, insect repellents, perfumes and cosmetics. As a proof of benzyl benzoate utilization inside of the car, a paint attack with benzyl benzoate was performed. The test revealed that, the part's failure was similar to that seen in the returned part from the car in warranty period. Highlights: The blisters occurrence was caused by benzyl benzoate, used in topical medications and it penetrated the coating of the part. A paint attack with benzyl benzoate was performed. The part's failure was similar to that seen in the returned part. Benzyl benzoate is a chemical that is not used within a manufacturing company of painted parts